SOSIALISASI PERENCANAAN BANGUNAN SEDERHANA TAHAN GEMPA - Soni Fajar Mahmud; Nuryasin Abdillah; Sony Adiya Putra (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2022)
Indonesia is located in an area with a high level of earthquake activity. Damage to buildings caused by the earthquake was caused by low quality materials and construction techniques that were not in accordance with construction rules. Lack of knowledge and understanding of construction workers on building techniques will lead to low building quality. The method used is lectures and discussions through socialization and direct field observations carried out together with training participants. This service aims to increase the competence of construction workers, which can be carried out through a socialization program on earthquake-resistant building planning. The socialization of increasing the competence of construction workers on building techniques according to the rules of earthquake-resistant building construction is one of the strategies for reducing (mitigation) disaster risk. The result of this service is an increase in technical understanding, especially in understanding the philosophy of earthquake-resistant building construction and technical implementation in accordance with the rules of construction science and established standards, especially regarding knowledge of iron circuits and connections/meetings, technical specifications, and concrete mixes.